Development of E-Learning in Web Programming Subjects for Moodle Based Vocational Students - Wicaksono, Ayyub; Florentinus, Totok Sumaryanto; Ahmadi, Farid (Innovative Journal of Curriculum and Educational Technology, 2020)
Along with the rapid development of information technology (IT), the need for an IT-based concept and learning mechanism becomes inevitable. Therefore, one form of information technology has emerged, namely facilities for learning systems called e-learning. This research aims to describe the learning system of class XI RPL web in Vocational High School Ibu Kartini Semarang, develop e-learning in class XI RPL web programming in Vocational High School Ibu Kartini Semarang, measure the feasibility of e-development products learning in class XI RPL web programming subjects at Vocational High School Ibu Kartini Semarang, measuring the effectiveness of e-learning development products in web programming subjects in class XI RPL at Vocational High School Ibu Kartini Semarang. This study uses Thiagarajan model, and e-learning was developed through four stages, namely preliminary studies, development planning and validation, product trials, and final product determination. The process of evaluating the feasibility of instructional media by giving questionnaires to media experts, material experts, and respondents of trial use (students). The results showed that the developed e-learning had fulfilled the requirements and fulfilled the requirements to be used as learning media. The results of the pre-test calculation get the value of tvalue = 0.733 and ttable = 1.67 while the post-test results produce a value of tvalue = 2.986 and ttable = 1.67 so that the hypothesis that can be taken is H0 is rejected if tvalue > ttable that an increase in student learning outcomes. The results of the calculation of students' early and late learning interests in the use of e-learning, with an average percentage increase of 16.38% of the previous learning interest. Based on the above research, the implication in the field of curriculum development science is the use of technology in learning web programming following the development of education 4.0.